2020
DOI: 10.1155/2020/3589497
|View full text |Cite
|
Sign up to set email alerts
|

Picroside II Improves Severe Acute Pancreatitis-Induced Intestinal Barrier Injury by Inactivating Oxidative and Inflammatory TLR4-Dependent PI3K/AKT/NF-κB Signaling and Improving Gut Microbiota

Abstract: Background. Picroside II exerts anti-inflammatory and antidiarrheal effects for treating the diseases associated with oxidative injury. However, its function on pancreatitis-induced intestinal barrier injury remains unclear. Hypothesis/Purpose. We hypothesized that picroside II will have protective effects against pancreatitis-induced intestinal barrier injury by affecting oxidative and inflammatory signaling (Toll-like receptor 4- (TLR4-) dependent phosphatidylinositol 3-kinase (PI3K), protein kinase B (AKT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Several studies have demonstrated that the TLR4/NF-rB and PI3K/AKT signalling pathways commonly regulate inflammation. For example, Piao et al (2020) reported that picroside II promoted the intestinal barrier injury induced by severe acute pancreatitis in the rat model via inhibiting the TLR4dependent PI3K/AKT/NF-jB signalling pathway. Zhao et al (2014) demonstrated that the TLR4-mediated PTEN/PI3K/AKT/ NF-jB signalling pathway was associated with the activation of a neuroinflammatory response in rat hippocampal neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that the TLR4/NF-rB and PI3K/AKT signalling pathways commonly regulate inflammation. For example, Piao et al (2020) reported that picroside II promoted the intestinal barrier injury induced by severe acute pancreatitis in the rat model via inhibiting the TLR4dependent PI3K/AKT/NF-jB signalling pathway. Zhao et al (2014) demonstrated that the TLR4-mediated PTEN/PI3K/AKT/ NF-jB signalling pathway was associated with the activation of a neuroinflammatory response in rat hippocampal neurons.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Piao et al. ( 2020 ) reported that picroside II promoted the intestinal barrier injury induced by severe acute pancreatitis in the rat model via inhibiting the TLR4-dependent PI3K/AKT/NF-κB signalling pathway. Zhao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous studies, in our study, we found that TLR4 levels were remarkedly decreased in serum, intestinal and lung tissues of rats with acute intestinal injury, which were ameliorated by emodin treatment. TLR4/NF-κB pathway has been reported to be closely related to acute intestinal/lung injury [2,25,26]. The NF-κB family consists of five members: P50, P52, p65/RelA, RelB and c-Rel.…”
Section: Discussionmentioning
confidence: 99%
“…For the isolated and cultured cells, immunohistochemical staining was conducted to identify Ecs, according to a previously described method (20). The aforementioned cultured cells were fixed with 4% paraformaldehyde (Sangon Biotech.…”
Section: Identification Of Ecsmentioning
confidence: 99%